(untitled) (Physical Education, Health and Social Sciences, 2025)
This research explores the effects of psychological safety at work on job satisfaction and self-efficacy among 300 educators from schools, colleges, and universities in Rawalpindi and Islamabad. With the help of standardized scales, results indicated a strong positive relationship between psychological safety, job satisfaction, and self-efficacy. Regression analysis indicated that psychological safety was a significant but weak predictor of self-efficacy of job satisfaction. Gender differences were minimal, but males reported slightly higher scores, with no significant differences among levels of teaching. The findings highlight the significance of promoting psychological safety to improve educators’ well-being and organizational performance. Organizational strategies to enhance psychological safety must be investigated in future studies. Keywords: Psychological safety, self-efficacy, job satisfaction.